2021
DOI: 10.1039/c9fd00147f
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of graphitic carbon nitride photocatalysts for water splitting

Abstract: A series of structures based on graphitic carbon nitride (g-C3N4), a layered material composed of linked carbon-nitrogen heterocycles arranged in a plane, were investigated by density functional theory calculations. g-C3N4...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…For example, if the band gap is reduced, then the material can absorb photon in the visible range. This can be achieved by either doping or manipulating the side chains/functional groups as in the covalent organic frameworks. , It has been also reported that doping of g-C 3 N 4 improves its photocatalytic activity in the water splitting reactions. , However, to the best of our knowledge, there is no systematic study on the effect of extra-framework cations on the band gap of PHI-based materials. In this paper, we employed DFT-based calculations to study the electronic structures of K-PHI and systems, where K + is replaced by H, Au + , Mg 2+ , and Ru 3+ , as well as the applicability of these materials in the photocatalysis of water splitting reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the band gap is reduced, then the material can absorb photon in the visible range. This can be achieved by either doping or manipulating the side chains/functional groups as in the covalent organic frameworks. , It has been also reported that doping of g-C 3 N 4 improves its photocatalytic activity in the water splitting reactions. , However, to the best of our knowledge, there is no systematic study on the effect of extra-framework cations on the band gap of PHI-based materials. In this paper, we employed DFT-based calculations to study the electronic structures of K-PHI and systems, where K + is replaced by H, Au + , Mg 2+ , and Ru 3+ , as well as the applicability of these materials in the photocatalysis of water splitting reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations of g -C 3 N 4 stretch over the past 13 years and feature a myriad of different g -C 3 N 4 structures and configurations. From pristine g -C 3 N 4 to its defected or chemically doped counterparts, the contemporary literature features theoretical efforts on g -C 3 N 4 monomers, monolayers, , bilayers, and periodic systems (also see comprehensive reviews ). These studies demonstrate that through computational modeling systematic predictions of g -C 3 N 4 properties can be attained that are both enlightening and highly applicable to real experimental systems, which can contain considerable variations in structure or may be difficult to access synthetically.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] Fortunately, the construction of heterojunctions or modications can improve the aforesaid problems. 29 The separation and storage of the generated hydrogen molecules in the photocatalytic water splitting processes are also crucial. In order to avoid the reverse reaction and possible dangerous explosion, hydrogen should be isolated from the oxygen products during water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…21–28 Fortunately, the construction of heterojunctions or modifications can improve the aforesaid problems. 29…”
Section: Introductionmentioning
confidence: 99%